Universality in volume-law entanglement of scrambled pure quantum states - Yuya O. Nakagawa (Nature Portfolio, 2018)
The entanglement in a quantum system between a small region and the surrounding environment contains details about the whole state. Nakagawa et al. find a formula for the entanglement entropy of a class of thermal-like states and show that it can be applied more broadly to identify equilibrating states.